Bioethics dialogue in assisted reproductive techniques - León Correa, Francisco J. (Acta Bioethica, 2007)
In assisted reproductive techniques two moral agents are confronted in informed dialogue: the medical team and the couple with infertility or sterility problems. The offspring in this dialogue is a basic human rights for both parts. There is danger of scientificism and of giving excessive importance to the commercialization of these techniques. Furthermore, it is necessary to establish the conditions to respect the rational ethical norms of discourse in the physician-patient dialogue, under the dialogical ethical perspective and to consider the interests and rights of the offspring as "the other" present-absent. The personalized bioethics perspective and the ethics of basic goods may complement the ethical dilemma's analysis related to assisted reproductive techniques.